(untitled) (Annals of Medical Research, 2022)
Aim: The aim of the current study was to assess the effects of platelet apheresis (PA) on cardiac autonomic control by the means of short-term heart-rate variability (HRV) technique. Materials and Methods: A total of 100 platelet donors (age: 29.0±0.9 years, body mass index: 25.8±0.7) were evaluated for heart rate (HR), HRV and blood pressure through a full cycle of PA. HR and HRV were assessed by 5-min continuous electrocardiographic recordings at four occasions, i.e., 5 min before (-5 min), and at 10th min (10 min), 45th min (45 min) and at post 5th min of PA. Time- and frequency-domain parameters of HRV were calculated using specific software. Low-frequency (LF)/high-frequency (HF) ratio was also determined. Blood pressure (BP) was also recorded 5 min before and 5 min after PA. Results: HR increased towards 45th min and declined towards the end of the PA (P<0.05). Both time- and frequency-domain parameters decreased towards the 45th min and increased towards the last 5th mins (P<0.05). LF/HF was increased towards 45th min and declined towards the end of the PA. Systolic BP decreased from 111 (106-120) mm Hg to 107 (99-115) mm Hg (P=0.003). Conclusions: HR, HRV and blood pressure were dynamically changed throughout the process of PA. These changes appeared to be caused by increased cardiac sympathovagal balance, resembling the pattern observed during whole blood donation.